Production of ethanol from sugarcane molasses using a multistage continuous fermentor - Salvacion, Jonathan W. DL. (1989)
The performance of a multi-stage continuous fermentor was investigated on the basis of product concentration, sugar utilization and productivity. Ethanol and sugar utilization was found to increase with feed molasses concentration. Overall productivity was limited by cell wash out. Ethanol concentration in the effluent increased while residual sugar decreased as the number of stages were generally required for the effective performance of the reactor. Cell was out was found to be the main problem, causing instability and reduced production of ethanol at high flow rates. Maximum ethanol concentration was obtained at .562 L/h from a feed concentration of 30 Brix.
Typescript.
Thesis (M.S.)--University of the Philippines Diliman.
Keywords: Alcohol; Fermentation; Molasses; Sugarcane